Noncontact Knee Soft-Tissue Injury Prevention Considerations and Practical Applications for Netball Players. Issue 3 (June 2021) - Mullally, Elaine M.; Clark, Nicholas C.
Abstract : ABSTRACT: Netball is a team sport played worldwide. High-risk landing events containing biomechanical potential for noncontact knee soft-tissue injury (STI) occur frequently. Subsequently, noncontact knee STI is common after knee abduction collapse during landing tasks. Lower-limb mobility, strength, balance, movement, and hop test characteristics (intrinsic, modifiable risk factors) are associated with high-risk landing biomechanics and noncontact knee STI events. Such risk factors should be considered in netball-specific noncontact knee STI prevention preparticipation screening. Corresponding training methods should be included as indicated in netball-specific multimodal noncontact knee STI prevention programs. This article provides insight into noncontact knee injury–related aspects of netball and gives detailed suggestions for injury prevention screening and programming.